2021
DOI: 10.1093/jrr/rrab057
|View full text |Cite
|
Sign up to set email alerts
|

MHY1485 enhances X-irradiation-induced apoptosis and senescence in tumor cells

Abstract: The mammalian target of rapamycin (mTOR) is a sensor of nutrient status and plays an important role in cell growth and metabolism. Although inhibition of mTOR signaling promotes tumor cell death and several mTOR inhibitors have been used clinically, recent reports have shown that co-treatment with MHY1485, an mTOR activator, enhances the anti-cancer effects of anti-PD-1 antibody and 5-fluorouracil. However, it remains unclear whether MHY1485 treatment alters the effects of radiation on tumor cells. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…To date, the utility of numerous ICIs, molecularly targeted drugs, and oncolytic viruses, among other therapeutic modalities, has been verified in clinical trials and preclinical models exploring the potential of combination therapy involving immunotherapy and RT 43 , 44 . Our results suggest that MHY1487, a radiosensitizer and an mTOR activator 39 , and Reolysin, an oncolytic virus derived from dsRNA 45 that is currently being studied in phase II and III trials for NSCLC and head and neck squamous cell carcinoma (NCT01708993 and NCT01166542), might be effective additions to combination therapy comprising immunotherapy and RT. Thus, elucidation of the molecular mechanism of the antitumour immune reaction is an important step in optimising RT combined with immunotherapy.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…To date, the utility of numerous ICIs, molecularly targeted drugs, and oncolytic viruses, among other therapeutic modalities, has been verified in clinical trials and preclinical models exploring the potential of combination therapy involving immunotherapy and RT 43 , 44 . Our results suggest that MHY1487, a radiosensitizer and an mTOR activator 39 , and Reolysin, an oncolytic virus derived from dsRNA 45 that is currently being studied in phase II and III trials for NSCLC and head and neck squamous cell carcinoma (NCT01708993 and NCT01166542), might be effective additions to combination therapy comprising immunotherapy and RT. Thus, elucidation of the molecular mechanism of the antitumour immune reaction is an important step in optimising RT combined with immunotherapy.…”
Section: Discussionmentioning
confidence: 84%
“… 12 ; however, our results led us to reject this hypothesis. Recent reports stated that irradiation induces mTOR activation 39 and that mTOR inhibition suppresses virus replication in vitro and in vivo 40 , 41 . We found that inhibition of the mTOR pathway resulted in the downregulation of the viral replication pathway, LTR expression and the phosphorylation of proteins associated with viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Han et al showed that the activation of mTOR signaling using MHY1485 treatment increased the 5-fluorouracil sensitivity of colon cancer cells deficient for p53 [ 65 ]. Furthermore, Lue et al reported that MHY1485 treatment inhibited growth and colony formation, in both cell lines under irradiation and non-irradiation conditions [ 66 ]. However, our study is the first that used MHY1485 for anti-tumor stem cells purposes and confirmed that mTOR can suppress CSCs, by inhibiting the autophagic process.…”
Section: Discussionmentioning
confidence: 99%
“…Senolytics, likes fisetin and quercetin both at centration of 40 μM, enhanced the sensitivity of radioresistant cells to radiotherapy by attenuating the senescence level [ 77 ]. MHY1485(10 μM), a mTOR activator, added to radiotherapy could induce significant higher oxidative stress-derived senescence than radiotherapy alone [ 78 ].…”
Section: Oxidative Stress and Senescence In Cancer Therapymentioning
confidence: 99%